Uncovering Language Learning Strategies and Their Link to Academic Success (a Case Study of KIP-Assisted Students in a Vocational School in Babat, Lamongan) - Angela Sulistiyowati Putri; Buyun Khulel (MEDIA DIDAKTIKA, 2026)
This study explores the learning strategies used in English learning by the vocational high school students who were supported with KIP money in Babat, Lamongan. While the financial support from KIP has improved access to education, the learning outcomes are leaving students with incomplete literacy skills and far away from declared welfare statuses, especially with respect to foreign language learning and language acquisition. The study employed a qualitative descriptive case study design, and involved 45 KIP students in Babat, Lamongan, and SILL questionnaire, interviews, and academic performance data were collected. The study found the most common strategies were metacognitive strategies (which included planning, self-regulating, and effective monitoring), and highest achievers and lower achievers were more likely to use social strategies. Different constraints of contexts played a role among students' variables for participating in learning, such as having materials and supportive parents, and those using internal regulation, were able to demonstrate great academic resilience to learn English. This study concludes that learning strategies for English learning, particularly metacognitive strategy, are only a few causes of English achievement based on learned behaviour, access, and material and monetary assistance.